A GHG management professional's take: CEQ's guidance for climate change and NEPA 1. (2nd January 2017) - Huxley, Doug
ABSTRACT: After two draft documents and more than seven years, in the August 5, 2016 edition of the Federal Register, the White House Council on Environmental Quality (CEQ) published final guidance for federal agencies to incorporate greenhouse gas (GHG) emissions and climate change into National Environmental Policy Act (NEPA) reviews. Questions and legal opinions on the final guidance are plentiful. Is the final guidance consistent with existing case law, is it binding, will it adequately protect agencies and project proponents from litigation, or does it require agencies to force reductions on project proponents? Questions and opinions aside, this article focuses on the practical implications of the final guidance—how environmental professionals can prepare NEPA reviews that align with its spirit and intent, meaningfully assess potential impacts and compare alternatives, and maintain consistency with established GHG accounting principles.